The Impact of Sustainable CRM Practices on Passenger Satisfaction and Loyalty in the Indian Airline Sector - Gidwani, Aanchal Bhagwan (Digital Repository of Theses, 2026)
This dissertation will analyse how Customer Relationship Management (CRM) contributes to passenger satisfaction, loyalty, and sustainability perceptions in the Indian airline industry. This study uses an interpretivist, qualitative research design in response to the growing aviation expansion, growing customer expectations, and growing competition. Qualitative Conceptual framework semi-structured interviews and Manual Thematic Coding were used to collect data which enabled in-depth research on lived experience of passengers and perceptions towards trust, service expectations and relational outcome to Indian airlines. The thematic analysis has identified four overriding loyalty drivers among Indian passengers: (1) environmental responsibility and sustainability, (2) trust, transparency, and privacy of data, (3) individualisation, customised interaction, and acknowledgment, and (4) responsiveness, empathy and service recovery. All these themes underscore the importance of emotional bonding, ethical behaviour, and valuable interaction in long-term customer loyalty. The article is significant because it introduces an Indian aviation-oriented CRM Conceptual frame, and it provides a foreseeable implication to airlines who want to enhance their customer loyalty based on qualitative and people-focused CRM practises.